Antimicrobial effect of plant extracts from native plants of Moyobamba against pathogenic microorganisms - Palomino Huarcaya , Roger Alberto (2025)
Objective: To evaluate the antimicrobial effect of plant extracts from native species of Moyobamba against clinically relevant pathogenic microorganisms. Material and Methods: Samples from five plant species were collected, and extracts were obtained through maceration with solvents of different polarities. A phytochemical analysis was performed to identify secondary metabolites, and antimicrobial activity was assessed using well diffusion and broth microdilution methods against Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica, Staphylococcus aureus, and Klebsiella pneumoniae. Results: Only the bark extract of Indano (Byrsonima crassifolia) exhibited antimicrobial activity, inhibiting exclusively S. aureus with a minimum inhibitory concentration (MIC) of 0.195 mg/mL. Conclusions: The bark of B. crassifolia contains compounds with antibacterial potential against S. aureus, supporting its traditional use. Further studies are needed to isolate the active principles and evaluate their therapeutic application.